2018
DOI: 10.14569/ijacsa.2018.091238
|View full text |Cite
|
Sign up to set email alerts
|

Hyper Parameter Optimization using Genetic Algorithm on Machine Learning Methods for Online News Popularity Prediction

Abstract: Online news is a media for people to get new information. There are a lot of online news media out there and a many people will only read news that is interesting for them. This kind of news tends to be popular and will bring profit to the media owner. That's why, it is necessary to predict whether a news is popular or not by using the prediction methods. Machine learning is one of the popular prediction methods we can use. In order to make a higher accuracy of prediction, the best hyper parameter of machine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 17 publications
(26 reference statements)
0
24
0
1
Order By: Relevance
“…Here we used a genetic algorithm for stochastic optimization of both MLP and CNN methods. Evolutionary algorithms such as GA are a well-documented alternative to solve complex optimization problems in a faster manner than an exhaustive grid-search procedure (Wicaksono and Supianto, 2018;Han et al, 2020) by selecting, combining, and mutating the model parameters sequentially, thus, mimicking mechanisms that resemble biological evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Here we used a genetic algorithm for stochastic optimization of both MLP and CNN methods. Evolutionary algorithms such as GA are a well-documented alternative to solve complex optimization problems in a faster manner than an exhaustive grid-search procedure (Wicaksono and Supianto, 2018;Han et al, 2020) by selecting, combining, and mutating the model parameters sequentially, thus, mimicking mechanisms that resemble biological evolution.…”
Section: Discussionmentioning
confidence: 99%
“…They used GA to obtain the parameters of ML algorithms. As stated in this study, optimum hyperparameters were obtained using GA in a shorter computation time than grid search [21].…”
Section: Hyperparameter Optimization Using Genetic Algorithm (Ga)mentioning
confidence: 99%
“…This helped the GA process to explore the domain properly and to boost local fine-tuning. Moreover, Wicaksono et al (2018) completely discussed the benefits of GA over GS in comprehensive research on hyperparameter optimization of different ML algorithms. Consequently, this study revealed that GA could be almost as accurate as GS but could significantly decrease the computational costs, particularly when the solution domain is quite large.…”
Section: Introductionmentioning
confidence: 99%